Corpus pragmatics - Landert, Daniela; Dayter, Daria; Messerli, Thomas C.; Locher, Miriam A. (Cambridge Elements Elements in pragmatics, 2023)
This Element discusses the challenges and opportunities that different types of corpora offer for the study of pragmatic phenomena. The focus lies on a hands-on approach to methods and data that provides orientation for methodological decisions. In addition, the Element identifies areas in which new methodological developments are needed in order to make new types of data accessible for pragmatic research. Linguistic corpora are currently undergoing diversification. While one trend is to move towards increasingly large corpora, another trend is to enhance corpora with more specialised and layered annotation. Both these trends offer new challenges and opportunities for the study of pragmatics. This volume provides a practical overview of state-of-the-art corpus-pragmatic methods in relation to different types of corpus data, covering established methods as well as innovative approaches. This title is also available as Open Access on Cambridge Core.